Neoplasias do trato alimentar superior em bovinos associadas ao consumo espontâneo de samambaia (Pteridium aquilinum) - Souto, Marione de Albuquerque Moreira (2005)
Thirty bovine with neoplasms of the upper digestive tract (UDT) associated to the spontaneous consumption of bracken fern (Pteridium aquilinum) were studied. They were from 27 farms, localized in the municipalities of Jaguari (23) and Nova Esperança do Sul (4), Rio Grande do Sul, Brazil. The total bovine population in those farms was 1,090 and large amounts of bracken fern were found in the pastures. Twenty-six were cows e four were castrated males. The age ranged from 3 to 13-years-old. Most of them were 7 to 8-years-old (46,6%). Clinical signs observed in the affected animals were progressive weight loss, absence of ruminal movements, cough, dysphagia, regurgitation, halitosis, diarrhea, and bloat. Less frequent signs were selective appetite, dyspnea, and salivation. Two bovines died and 28 were euthanatized in extremis and submitted to necropsy. The main gross and microscopic findings were found in the same areas of the UDT. They were digestive papillomatosis, transforming papillomas, and squamous cell carcinomas (SCC). Twenty-nine bovines had papillomas of various sizes in several areas of the UDT. The digestive papillomatosis ranged from mild (45%), to moderate (38%), to severe (17%). Three developing phases were observed microscopically in the examined papillomas: an early growing phase, a developing phase, and a regressing phase. The regressing phase was characterized by lymphocytic infiltrates at the base of the papilloma. In 16 cases, the microscopic examination of lesions grossly resembling papillomas (although some were slightly round, with lower or ulcerated finger-like projections) revealed malignant transformation of the papillomas into SCCs. The SCCs were solitary (12/30) or multiple (18/30) and were histologicaly characterized as well, moderately, or poorly differentiated. Grouping the distribution of SCCs of larger extension in the UDT into cranial region (base of the tongue, pharynx/oropharynx, and epiglottis), medial region (esophagus), and caudal region (cardia and rumen), the distribution was cranial in 39%, middle in 16%, and caudal in 45% of the cases. By the same grouping criteria, but considering the total number of times SCCs of varied extensions were diagnosed in the cranial, middle, and caudal regions, the percentages changed to 34%, 26%, and 40%, respectively. Metastases to regional lymph nodes and other organs, like liver and lungs, were observed in 18 cases. Immunohistochemistry for cytokeratin was performed in selected sections of SCCs and metastases, showing strong positive reaction in the well and moderately differentiated SCCs, but weak positive reaction in the poorly differentiated ones. The epidemiological and histomorphological evidences showed in this study are in agreement with the observations that point out the co-carcinogesis between bovine papillomavirus type 4 infection and chemicals of bracken fern in the pathogenesis of the SCCs in the UDT of cattle.